A Complex Confucian Conception of Distributive Justice. - Jin, Hui (Philosophia, 2023)
Distributive justice is generally important to persons in society. This was widely recognized by early Confucian thinkers, particularly Confucius, Mencius, and Xunzi, in ancient China. Confucius, Mencius, and Xunzi had developed, in varying degrees and with different emphases, their respective conceptions of distributive justice to address the relevant social problems in their times. These conceptions not only are intrinsically valuable political thoughts, but may prove useful in dealing with current or future social issues. Thus in this essay, first I provide a detailed interpretation of each of those thinkers' conceptions of distributive justice, then I combine some essential elements of those conceptions to form a general and coherent conception, which is called a complex Confucian conception of distributive justice, and finally I evaluate this conception by considering some of its implications and limitations, in theory and in practice. This aims mainly at exploring the meaning and practical bearing of basic Confucian conceptions of distributive justice.